The legality of the use of cyber-attacks in international conflicts and international responsibility for them - Deham, Mohammed; Khalil, Mahmood (Journal of Legal Sciences, 2022)
The emergence of the computer and the expansion of the use of the Internet in all areas of life The various negative effects and risks arising from this expansion will appear, as the greater the reliance On these technologies in development, the greater the risks associated with protecting information, and with increasing Global reliance on information and communication technology, especially with regard to the governmental aspect Countries are vulnerable to attacks through cyberspace, as it has become and public facilities, it has also increased This space is vulnerable to violations by network intruders, whether they are countries, organizations or individuals. Hence, it has become necessary to research the legality of using this type of attack, especially During an armed conflict between two countries.